Gender-based cyber violence, gender and political literacy - Hrnčić, Jasna H.; Lončar, Nina Z.; Gajić, Miona G. (Sociološki pregled, 2025)
Gender-based cyber violence (GBCV) disproportionately affects women, leaving impacts on the victims’ quality of life, academic achievement, mental health, and public and political engagement, thus exacerbating social inequalities. The study aims to determine the prevalence of GBCV and its association with gender and political literacy, measured by university education. A total of 506 students of General Political Studies (GPS) and Social Policy and Social Work Studies (SPS&WS) completed the questionnaire online, with 12 forms of GBCV. Female students were more likely to experience eight forms of GBCV. Among female students, those studying GPS were more frequently victimized by six forms of GBCV than those studying SPSWS. Among female students of GPS, those with a higher level of education experienced eight forms of GBCV more often than those with a lower level of education. These gender inequalities lead to the silencing of women in public spaces.